Using Mind Mapping to Improve Students' Writing Skills of the Eleventh Grade at MAS Yaspen Nurul Huda Serapuh ABC in the Academic of the Year 2023 - Julia Dewi; Donny Adiatmana Ginting; Rosmen; Fernando De Napoli Marpaung (English Lecturers and Teachers Association (ELTA), 2023)
The aim of this study is to investigate the use of mind mapping as a tool to improve the writing skills of students in Yaspen Nurul Huda Serapuh ABC 2023. Four students with writing difficulties participated in the study. In the study, researchers used observational techniques to determine students’ writing abilities through mind mapping. Teacher performed descriptive analyzes of students’ writing test scores before and after they applied the ”mind mapping” technique in their writing. The purpose of this study was also to determine the effectiveness of mind mapping in teaching writing. The results of this study provide insight into the effectiveness of using mind mapping in writing classes in these schools to improve students writing skills. Keywords: using mind mapping, improve students’ skills, results of study